An analysis on the diversity of zooplankton in shipping areas of cochin estuary with special reference to marine non-indigenous species - Riyas, Rahman P.K (KUFOS, 2018)
Abstract- Zooplankton occupy a prominent position in marine food webs, modulating energy availability to higher trophic levels, while themselves being affected by environmental variation. This study was carried out to analyze the diversity of zooplankton is ship berthing area and shipping channels with a view to identify the presence of non-indigenous species (NIS) is present in the zooplankton community in Cochin estuary. The study was carried out in in five different stations during the pre monsoon season and the diversity and abundance of zooplankton were observed along with important physico-chemical parameters. Among the parameters monitored, Sea Surface Salinity (SSS), nutrient and biomass showed significant difference between the stations during the study period. SSS was found to be high with an average value of 28.45 ± 1.23. All the stations showed similar species richness and number of species but differed in diversity, overall abundance and evenness of populations. A total number of 17 zooplankton groups were observed which were then clustered Phylumwise for statistical analysis. Arthropoda dominated the community with an average composition of 93.8% followed by Phylum Chordata at 3.2% and Phylum Mollusca at 1.8%. Copepods constituted 42.2 – 92.3% of arthropods followed by cirriped larvae with 0.8 – 27.8% in different stations, which corroborated with earlier studies of zooplankton diversity in this area. Other groups of zooplankton in Phylum Chaetognatha, Cnidarians and Annelids also showed zooplankton diversity which conformed with earlier observations. Salinity was found to influence zooplankton community the most, but smaller groups were found less dependent on it. No NIS was identified in the study and it is postulated that the well-established populations of zooplankton groups and diversity of the ecosystem might be resisting the establishment of NIS in the region. The present study provides a bench-mark data on the species assemblage of zooplankton in the region and necessitates a detailed study on the trophic level interaction among these communities. Since the health of zooplankton population in the region is rather robust, any non-invasive groups establishing in the region would require occupying a specific trophic level, displacing existing native group for which further in depth study is warranted.